PERBANDINGAN KONSTRUKSI PEMBERITAAN KASUS KAUS BOM ATOM BTS DALAM MEDIA MASSA JEPANG ASAHI.COM DAN MAINICHI.JP - Adis Kusumawati (Universitas Airlangga, 2019)
A popular boy group from South Korea BTS was being criticized because one of the member once wore a t-shirt with words and image graphic desgin that considered hurting the atomic bomb victims' feeling. This controversy lead to a performance cancellation of theirs in a music broadcast